2021
DOI: 10.1088/1361-648x/ac34ae
|View full text |Cite
|
Sign up to set email alerts
|

2D and 3D double perovskite with dimensionality-dependent optoelectronic properties: first-principle study on Cs2AgBiBr6 and Cs4AgBiBr8

Abstract: Recently, the effect of dimensional control on the optoelectronic performance of two-dimensional (2D)/three-dimensional (3D) single perovskites has been confirmed. However, how the dimensional change affects the photoelectric properties of 2D/3D all-inorganic double perovskites remains unclear. In this study, we present a detailed theoretical research on a comparison between the optoelectronic properties of 3D all-inorganic double perovskite Cs2AgBiBr6 and recently reported 2D all-inorganic double perovskite C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Replacing conventional energy sources with fossil fuels, including lithium-ion batteries (LIB), solar cells (solar cells), supercapacitors (SC), nanogenerators (NG), biofuel cells (BFC), and photodetectors (PDs) [17], is therefore necessary to develop self-powered systems to meet the growing demand for long-term energy use in different environmental scenarios [18][19][20]. With the development of integrated power plant, small, light, high-density and high-reliability energy systems will be better combined [21][22][23]. For example, LIB and solar cell, if a new perovskite material with excellent photovoltaic effect is designed into an integrated dual-function device, it will have a broad development prospect in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Replacing conventional energy sources with fossil fuels, including lithium-ion batteries (LIB), solar cells (solar cells), supercapacitors (SC), nanogenerators (NG), biofuel cells (BFC), and photodetectors (PDs) [17], is therefore necessary to develop self-powered systems to meet the growing demand for long-term energy use in different environmental scenarios [18][19][20]. With the development of integrated power plant, small, light, high-density and high-reliability energy systems will be better combined [21][22][23]. For example, LIB and solar cell, if a new perovskite material with excellent photovoltaic effect is designed into an integrated dual-function device, it will have a broad development prospect in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, Chen et al studied the photoelectric properties of 2D inorganic double perovskite Cs 4 AgBiBr 8 and confirmed that it is more suitable for luminescence application than 3D all-inorganic double perovskite. 15 Murgulv et al theoretically investigated the detection performance of X-ray, revealing that the double perovskite (BA) 2 CsAgBiBr 7 has great potential in the biomedical field. 16 Palummo et al theoretically revealed electronic and optical properties of a pair of Pb-free 2D layered hybrid perovskites, (BA) 4 AgBiBr 8 and (BA) 2 CsAgBiBr 7 , indicating that the 2D compounds can be used as polarization sensitive optical devices.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, all-inorganic halide perovskites, especially the double perovskite, without molecules and lead-free perovskite showing excellent stability against moisture, heat, and light, have attracted extensive attention [ 1 , 2 , 3 ]. In general, since the 2D all-inorganic double perovskite Cs 4 AgBiBr 8 has a high exciton-binding energy, which is 3 times larger than that of the 3D all-inorganic double perovskite Cs 2 AgBiBr 6 , the charge carrier mobility and absorption coefficients of Cs 4 AgBiBr 8 (2D) in the visible spectrum are worse than those of Cs 2 AgBiBr 6 (3D) [ 4 ]. However, in 2021, Wang et al reported the upconversion photovoltaic effect of WS 2 monolayer/(C 6 H 5 C 2 H 4 NH 3 ) 2 PbI 4 2D perovskite heterostructures by below-bandgap two-photon absorption via a virtual intermediate state, which enables heterojunction devices with good photoresponsivity and excellent current on/off ratio [ 5 ].…”
Section: Introductionmentioning
confidence: 99%